2022
DOI: 10.1038/s41420-021-00801-9
|View full text |Cite
|
Sign up to set email alerts
|

Canagliflozin protects against cisplatin-induced acute kidney injury by AMPK-mediated autophagy in renal proximal tubular cells

Abstract: Sodium-glucose cotransporter 2 inhibitors, which are recently introduced as glucose-lowering agents, improve cardiovascular and renal outcomes in patients with diabetes mellitus. These drugs also have beneficial effects in various kidney disease models. However, the effect of SGLT2 inhibitors on cisplatin-induced acute kidney injury (AKI) and their mechanism of action need to be elucidated. In this study, we investigated whether canagliflozin protects against cisplatin-induced AKI, depending on adenosine monop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 53 publications
0
12
2
Order By: Relevance
“…However, their results were only confined to markers related to autophagy and apoptosis. 33 Unlike our results, few studies suggested that activation of AMPK which occurs normally following Cis administration in response to oxidative stress leads to p53 activation and apoptosis in renal cells. 34 On the contrary, accumulating research confirmed that Cis activates AMPK to induce autophagy that results in reduced apoptosis and protects against kidney injury.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…However, their results were only confined to markers related to autophagy and apoptosis. 33 Unlike our results, few studies suggested that activation of AMPK which occurs normally following Cis administration in response to oxidative stress leads to p53 activation and apoptosis in renal cells. 34 On the contrary, accumulating research confirmed that Cis activates AMPK to induce autophagy that results in reduced apoptosis and protects against kidney injury.…”
Section: Discussioncontrasting
confidence: 99%
“…They used an AMPK inhibitor as well to confirm that activation of AMPK is the pathway responsible for renal protection. However, their results were only confined to markers related to autophagy and apoptosis 33 . Unlike our results, few studies suggested that activation of AMPK which occurs normally following Cis administration in response to oxidative stress leads to p53 activation and apoptosis in renal cells 34 .…”
Section: Discussioncontrasting
confidence: 97%
“…First, SGLT2 inhibitors consistently enhance autophagic flux (including mitophagy) in the heart and kidney; the action to augment autophagy is seen in tissue harvested from chronically treated animals as well as in isolated cell cultures perfused with SGLT2 inhibitors (Table 1). [155][156][157][158][159][160][161][162][163][164][165][166][167][168][169][170][171][172][173] Second, SGLT2 inhibitors mute the generation of reactive oxygen species, enhance antioxidant mechanisms, and mitigate endoplasmic reticulum stress. 165,167,169,[174][175][176] Third, SGLT2 inhibitors accelerate the disposal of injured mitochondria, restore healthy mitochondrial function, and promote mitochondrial biogenesis 167,169 ; the increase in mitochondrial mass is a characteristic feature of the action of these drugs on electron microscopy.…”
Section: Action Of Nutrient Sensors To Influence Cellular Stress By M...mentioning
confidence: 99%
“…The effect of SGLT2 inhibitors to reduce oxidative stress, enhance mitochondrial integrity, mute inflammatory pathways, and preserve cell viability is paralleled by an increase in expression or activity of AMPK, SIRT1, SIRT3, SIRT6, and PGC-1α and decreased activation of mTOR in diverse tissues under stress, particularly in experimentally induced cardiomyopathy and nephropathy (Figure 4 and Table 2). 48,54,57,76,77,87,110,157,158,161–171,174–219 The increase in AMPK and autophagic flux also explains the increase in ATP production that is seen in the heart and kidneys, both experimentally and clinically, after SGLT2 inhibition. 52,54,57,181,220…”
Section: Actions Of Sglt2 Inhibitors To Promote Nutrient Deprivation ...mentioning
confidence: 99%
“…70 Although dapagliflozin did not result in a statistically significant risk reduction of the composite end point of organ dysfunction or death, this agent was associated with a numerically reduced incidence of AKI than controls (3.4% vs. 5.5%). 71 Furthermore, a recent experimental study by Park et al 71 demonstrated that canagliflozin prevents cisplatin-induced AKI by activating adenosine monophosphate–activated protein kinase and inducing autophagy.…”
Section: Effects Of Sglt2 Inhibitors On Acute Kidney Injurymentioning
confidence: 99%